Effect of Semi Fowler and Right Lateral Position on Increased Oxygen Saturation in Adhf Patients in the CVCU Room of Dr. M. M Dunda Limboto Hospital - Nursila Rauf; Ita Sulistiani; Ibrahim Suleman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Acute Heart Failure (ADHF) is often found, namely Acute Decompensated Heart Failure (ADHF) is one of the health problems with a high morbidity and mortality rate, the symptoms that occur are difficulty breathing when resting during the treatment period. Non-pharmacological interventions such as body position regulation are alternatives used by nurses, The most commonly used positions are the semi-fowler and right lateral positions. The purpose of the study was to analyze the effect of the semi-fowler and right lateral position on the Increase in Oxygen Saturation in ADHF patients in the CVCU Room of Dr. M. M Dunda Limboto Hospital. This study is a quantitative research using a Quasi-Experimental, Pretest and Posttest Control group research design.The population in this study was patients treated in a CVCU room with ADHF. Sampling using accidental sampling was a sample size of 30. The research instrument used an oxygen saturation observation sheet. Analysis of univariate and bivariate data of frequency distribution tests and paired t-tests. The results showed a p value of 0.000 which means that there was an influence of the semi fowler and right lateral positions on the increase in oxygen saturation in ADHF patients in the CVCU Room of Dr. M. M Dunda Limboto Hospital. Patients with the right semi-fowler and lateral positions are advised to continue to monitor their oxygen saturation.